Real-Time Simulation of Hybrid Energy Solution for Microgeneration in Residential Buildings - Abrishambaf, Omid (2021)
The unplanned power outages have occurred for all of us, and we know that from the household inhabitant’s standpoint, power outage even for a short period of time is not pleasant. This matter is also true for the residential buildings that are far from the main cities, namely in the countryside or in a small village, and they may have a power outage for a long-term even with a small problem in the power transmission lines. Therefore, an energy solution module is required in order to prevent power outage for household inhabitants. In this paper, an off-grid energy sustainability solution for residential buildings will be represented by considering several small-scale generators. The module consists of several microgeneration units and energy storage systems for maintaining the energy balance. Also, a software-based control unit is used for controlling the production. The main focus is given to survey the performance of the wind turbine utilized in this energy module. The behavior of an induction machine and a permanent magnet machine will be investigated in two levels of simulation and emulation in order to realize the best solution for the wind turbine of presented energy module.